Intuition as Design Dialogue: Discovering a Language beyond Words - Teal, Randall (Enquiry The ARCC Journal for Architectural Research, 2008)
Henri Bergson considered the truest form of knowing to be attainable only through acts of intuition, as he believed the intuitive state created a direct connection to reality itself.For architecture, a field that is grounded in experience, it is important to balance the drive of the intellect with intuitive strategies, which help move toward the unification of data under an experiential aegis. Drawing primarily upon the writings of Bergson and Martin Heidegger, this paper describes how the reductive proclivities of the intellect tend to obscure the embodied insights of intuition, and how the listening response of intuition reveals a primal language that is activated by the immersed dialogue of one experiencing the world.